The Influence of Transformational Leadership, Work Motivation, and Work Stress on Employee Performance at The Representative Office of Bank Indonesia West Java Province in The Payment System Implementation Division - Nugraha, Riki Zajuli (Innovative: Journal Of Social Science Research, 2024)
This study aims to analyze the effect of transformational leadership, work motivation and work stress on employee performance. The research was conducted at the Representative Office of Bank Indonesia of West Java Province in the Payment System Implementation Division. The research method used is descriptive and verification analysis with a sample size of 67 people taken from the entire population. The sampling technique used is a saturated sample or census. This research was assisted by statistical software SPSS version 25.0 for Windows. This research was conducted by distributing questionnaires, interviews and observations as data collection techniques. Testing the questionnaire with validity test and reliability test. The analysis method uses classical assumption test, multiple linear regression analysis, and hypothesis testing. The results showed that Transformational Leadership has a positive and significant effect on Employee Performance, Work Motivation has a positive and significant effect on Employee Performance and Job Stress has a positive and significant effect on Employee Performance. So, the results of this study indicate that Transformational Leadership, Work Motivation and Work Stress have a positive and significant effect on Employee Performance at the Representative Office of Bank Indonesia of West Java Province in the Payment System Implementation Division.